Preparation and Characterization of Electrospun Food Biopackaging Films of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Derived From Fruit Pulp Biowaste - Melendez-Rodriguez, Beatriz; Castro-Mayorga, Jinneth L.; Reis, Maria A. M.; Sammon, Chris; Cabedo, Luis; Torres-Giner, Sergio; Lagaron, Jose M. (Frontiers in Sustainable Food Systems, 2018)
In the present study, circular economy based and potentially low-cost poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) was produced by mixed microbial cultures derived from fruit pulp, an industrial by-product of the juice industry. Three different chemical routes, namely non extraction, extraction with sodium hypochlorite (NaClO), and extraction with chloroform, in combination with filtering and centrifugation, were explored to purify the biopolymer and find the most optimal solution for its processing via electrospinning. The resultant ultrathin fiber mats of the different extracted PHBV materials were thermally post-processed at different temperatures in order to obtain continuous films adequate for food packaging applications. The resultant films were characterized in terms of morphology, crystallinity as well as thermal, mechanical, and barrier properties. The results showed that extraction with both chloroform and NaClO with a post-treatment of filtering and centrifugation of the PHBV containing biomass were necessary refining steps to allow its processing by electrospinning. In particular, the PHBV extracted with chloroform presented a higher degree of purity, resulting in more transparent films with lower wettability and higher flexibility. The here-formulated electrospun films made of biomass derived from biowaste exhibit great potential as interlayers or coatings for food biopackaging applications.